In-vitro Screening of Anti Parkinson’s Activity of Ethanolic Extract of Malaxis acuminata against Rotenone – Induced Toxicity in Sh-Sy5y Neuroblastoma Cell Lines - Venkatachalam, Gomathi; T L, Mary Sheeja; Balasundaram, Jaykar (Asian Journal of Biological and Life Sciences)
The study attempts to investigate in-vitro screening of anti-Parkinson’s activity of the entire plant of Malaxis acuminata by using the SH-SY5Y cell line. The powdered plant of Malaxis acuminata was extracted by the Soxhlet method using nonpolar to polar solvents. Rotenone (10μM) was used to induce toxicity on SH-SY5Y cell lines. The cell lines were then treated with 100μg, 50μg, 25μg, 12.5μg, 6.25μg of ethanolic extract of Malaxis acuminata and in a humidified 5 % CO2 incubator, the cells were inoculated at 37°C. When the doses were steadily increased over 24 hr, the percentage viability of the cells fell. 6.25g/ml was shown to be the most effective concentration for inhibiting cell proliferation. The number of viable cells tends to decrease as that the concentration of the extract increases. Malaxis acuminata ethanolic extracts exhibited antiparkinsonian activity on SH-SY5Y cell lines.
Keywords: Anti-parkinsonian activity; Jeevak; Malaxis acuminata; MTT assay.; Rotenone; SH -SY5Y cell lines